Faktor-faktor yang Mempengaruhi Kepatuhan Wajib Pajak Pedagang di PGS Surakarta - Bima Setyawan; Anita Wijayanti; Rosa Nikmatul Fajri (Universitas Batanghari Jambi, 2021)
This study aims to examine the factors that have an influence on tax compliance in PGS Surakarta because tax compliance in Surakarta is still low, especially for MSMEs. The independent variables used in this study are variables of tax understanding, tax awareness, tax amnesty, taxpayer attitudes, and tax sanctions on tax compliance. The population of this study were all MSMEs in PGS Surakarta. Meanwhile, the determination of the number of samples in this study used random sampling with 60 respondents. The data collection technique used in this study is to use a questionnaire and data analysis methods using multiple regression with analysis tools using SPSS. The results of this study indicate that partially and simultaneously the variables of tax understanding and tax amnesty have an effect on MSME tax compliance in PGS Surakarta. Meanwhile, tax awareness variables, taxpayer attitudes, and tax sanctions have no effect on taxpayer compliance at PGS Surakarta.